Risk of hypovolemia associated with sodium–glucose cotransporter-2 inhibitors treatment: A meta-analysis of randomized controlled trials - Rong, Xi; Zhu, Yawen; Wen, Bo; Liu, Kai; Li, Xinran; Gou, Qiling; Chen, Xiaoping (Frontiers in Cardiovascular Medicine, 2022)
Aim of the review To assess the risk of hypovolemia for sodium–glucose cotransporter-2 (SGLT2) inhibitors treatment. Method A systematic literature retrieval was performed in PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and Scopus from inception up to 4 October 2022, Data for study characteristics and outcomes of interest were extracted from each eligible study. Risk ratios (RRs) with a 95% confidence interval (CI) for hypovolemia were calculated using a random-effect model. Results A total of 57 studies (n = 68,622) were included in our meta-analysis, with a result of 1,972 hypovolemia incidents (1,142 in the SGLT2 inhibitors group and 830 in the control group). The pooled RR was 1.12 (95% CI: 1.02–1.22). It is evident that receiving SGLT2 inhibitors increased the risk of hypovolemia. When stratified by category of SGLT2 inhibitors the result was consistent; when the subgroup was analyzed by age, the pooled RR was 1.07 (95% CI: 0.94–1.23) in patients aged ≥65 years and 1.14 (95% CI: 1.02–1.28) in those aged <65 years. When comparing the baseline estimated glomerular filtration rate (eGFR) of less than or equal to 60 mL/min/1.73 m2 with a baseline eGFR greater than 60 mL/min/1.73 m2, the pooled RR was 1.21, (95% CI: 1.00–1.46) and 1.08, (95%CI: 0.98–1.20), respectively. Conclusion Our meta-analysis has demonstrated that SGLT2 inhibitors increased the risk of hypovolemia in patients with Type 2 Diabetes Mellitus (T2DM). It is necessary to pay attention to the risk of hypovolemia associated with SGLT2 inhibitors, especially in older individuals and those with moderate renal impairment. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42020156254].